Development of an integrated, holistic care package for people with lymphoedema for use at the level of the Primary Health Care Unit in Ethiopia. - Abraham Tesfaye; Maya Semrau; Oumer Ali; Mersha Kinfe; Mossie Tamiru; Abebaw Fekadu; Gail Davey (Public Library of Science (PLoS), 2021)
Background Neglected Tropical Diseases (NTDs) are a group of several communicable and non-communicable diseases prevalent in tropical and subtropical areas. The co-endemicity of these diseases, the similarity of their clinical signs, and the need to maximize limited financial and human resources suggest the importance of adoptingan integratedapproach to their prevention and treatment. Aims This study describes the development of a comprehensive package of physical, mental health and psychosocial care for people with lower-limb lymphoedema caused bypodoconiosis, lymphatic filariasis (LF)or leprosy as part of the EnDPoINT program in Ethiopia. Method The care package was developed using a mixed-methods approach, consisting of a literature review, situational analysis, Theory of Change (ToC) workshops, qualitative research, and additional workshops to fine-tune the draft care package. The care package was developed between March 2018 and January 2020 in Addis Ababa and the implementation research site, Awi zone in the North-West of Ethiopia. Results The holistic care package includes components implemented at three levels of the health care system:health organization, facility, and community. Sections of the care package are directed at strengthening capacity building, program management, community engagement, awareness-raising, stigma-reduction, morbidity management, disability prevention, follow-up visits, referral linkage, community-based rehabilitation, and monitoring and evaluation. Conclusions The study developed a holistic integrated care package for lower limb disorder and co-morbid mental health problems caused by podoconiosis, LF or leprosy. The approach has the potential to significantly reduce lower limb disorder-associated morbidity, disability, and psychosocial problems. It also standardizes a scalable approach appropriate for the Ethiopian setting and, most likely, other countries where these NTDs are present.